PENATALAKSANAAN HOLISTIK PASIEN REMAJA PUTRI USIA 19 TAHUN DENGAN TUBERKULOSIS MELALUI PENDEKATAN DOKTER KELUARGA DI WILAYAH PUSKESMAS RAWAT INAP SIMPUR - Ayu Paramita, Nadhea; Zuraida, Reni (Medula, 2024)
Tuberculosis (TB) is an infectious disease that is still a problem in developing countries. Worldwide. Although the government has implemented many programs for controlling the TB, the role of family physician is very important in treating TB. In dealing with these problems, the need for cooperation from various parties in a comprehensive and holistic manner. Implementing comprehensive and holistic family doctor services by identifying risk factors, clinical problems, and patient management based on evidence based medicine with strategies that are patient centered, family oriented and community oriented.The analysis of this study is a case report. Primary data were obtained through history taking, physical examination and home visits. Secondary data were obtained from aupporting investigation.The assessment is carried out based on a holistic diagnosis of the initial, process, and final study quantitatively and qualitatively. Patient Nn.N, 19 years old, came to the clinic with cough , easy fatigue, weight loss and night sweats since 2 months ago. The patient was diagnosed with clinically confirmed pulmonary tuberculosis. After the intervention, pulmonary TB complaints improved. There is a change in behavior towards the patient's disease where the quantitative assessment found an increase in all aspects assessed, namely knowledge, diet, and physical activity.